Microstructural characterisation and hardness of Fe-Mn alloys compared to commercial 9%Nickel alloy - Mampuru Lebedike; Phasha Maje; Bodunrin Michael; Klenam Desmond; Moema Joseph (MATEC Web of Conferences)
Increased energy demand globally due to population growth opens opportunities for alternative energy sources. Liquefied natural gas is gaining traction as an alternative to diversifying energy supply. 9%Nickel steel is used in the construction of tanks for storage and transportation of liquefied natural gas because of its high toughness and tensile strength properties. This alloy is not readily available because of its complex production process and high cost. In this research, cast Fe-Mn-based alloys are explored as an alternative to 9%Nickel steel. Computer-simulated binary compositions are cast and subjected to a thermomechanical process. Thermomechanically processed alloys are microstructurally assessed and harness tested as the initial evaluation step in selecting high-performing base alloy for further alloying. Alloy.